Peri‐ictal yawning: A potential lateralizing sign in temporal lobe epilepsy - Xiaoping Du; Yi Yao; Jiani Chen; Xiaoping Yang; Lei Zhang; Yingying Tang; Xiaoting Hao; Dong Zhou; Shizhong Lian; Fengpeng Wang; Xiaobin Zhang; Meizhen Sun; et al. (Epilepsia Open)
Abstract Objective The primary objective of this retrospective analysis was to evaluate the incidence and lateralization value of peri‐ictal yawning (PY) in people with temporal lobe epilepsy (TLE). PY has only occasionally been reported as a manifestation of focal epilepsy. We aimed to determine whether PY could serve as an indicator to help lateralize seizure onset during epileptic seizures. Methods Among 236 consecutive TLE patients admitted for video‐EEG monitoring, we analyzed the clinical characteristics, along with scalp video‐EEG, magnetic resonance imaging (MRI), fluorodeoxyglucose‐positron emission tomography (FDG‐PET), Wada test, and stereo EEG (SEEG) in patients with PY. Results Among the 236 patients, 26 (11.0%) exhibited PY, and 36 of 1018 recorded seizures (3.5%) were associated with PY. Of the 26 patients with PY, 19 (73.1%) had non‐dominant TLE, while 7 (26.9%) had dominant TLE. The majority of these patients presented with staring, arrest, and automatisms during their seizures with accompanying vegetative signs. PY occurred either during the ictal or postictal phase in all patients. Exception for 10 seizures (10/36, 27.8%) at the early stage (less than 25% total duration), PY was primarily linked to the late ictal and postictal phases. Surgical intervention was performed in 12 patients, 9 of whom (75%) achieved seizure freedom (Engel class I), with 7 of these 9 (77.8%) having non‐dominant TLE. Significance Yawning is a physiological phenomenon typically not associated with epilepsy. The present series suggests that PY is relatively uncommon in TLE, but may represent a rare vegetative sign, particularly in cases with non‐dominant TLE. Further investigation with a larger cohort of surgically confirmed cases and using intracranial EEG is essential to deepen our understanding of this phenomenon. Plain Language Summary Yawning is a typical physiological response that is generally not linked to epilepsy. However, it can occasionally indicate seizure activity, particularly in TLE. PY happens more often observed in non‐dominant TLE and usually occurs in the later stages of a seizure or just after it. It may hold potential as a lateralizing marker in TLE.